Stres i emocje studentów zarządzania - Turowska, Anna (Studia Edukacyjne, 2020)
The subjects were 196 final-year students of The Warsaw School of Economics Faculty of Management. The purpose of the study was to measure the dominant strategy of coping with stress moderated by positive, negative and ambivalent emotions. This can be of significance in the management of staff and organizations under often unpredictable economic conditions.